Multimodality imaging: Bird's eye view from The European Society of Cardiology Congress 2017, Barcelona, August 26-30, 2017 - Jeroen J. Bax; Victoria Delgado; Sven Plein; Juhani Knuuti; Stephan Achenbach (SPRINGER, 2022)
This year 2017, 396 imaging abstracts (43% of abstracts submitted under the topic of imaging) were presented at the European Society of Cardiology (ESC) congress, held in Barcelona from August 26th to 30th. For this bird’s eye view from this ESC meeting, experts in echocardiography (VD), cardiovascular magnetic resonance (CMR) (SP), nuclear imaging (JK), and cardiac computed tomography (CT) (SA) have selected the abstracts in their areas of expertise that were of most interest to them. These abstracts were integrated by one of the Editors of the Journal (JB).